2019
DOI: 10.1002/jemt.23282
|View full text |Cite
|
Sign up to set email alerts
|

Development of electrically conductive hybrid nanofibers based on CNT‐polyurethane nanocomposite for cardiac tissue engineering

Abstract: Conductive nanofibers have been considered as one of the most interesting and promising candidate scaffolds for cardiac patch applications with capability to improve cell–cell communication. Here, we successfully fabricated electroconductive nanofibrous patches by simultaneous electrospray of multiwalled carbon nanotubes (MWCNTs) on polyurethane nanofibers. A series of CNT/PU nanocomposites with different weight ratios (2:10, 3:10, and 6:10wt%) were obtained. Scanning electron microscopy, conductivity analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…The FTIR analysis indicated a decrease in the intensity of spectral peaks corresponding to methyl groups ( Figure 3 ), suggesting that the high concentration of CNTs at the films’ surface reduced the number of highly hydrophobic methyl groups of isobutylene. In the study by Shokraei et al [ 49 ], a nanocomposite of multiwalled CNTs and polyurethane nanofibers showed a reduction of the contact angle by increasing the concentration of CNTs as a result of dominant carboxyl groups on the surface. Another study reported an increase in the hydrophobicity of nanocomposites based on a polymer blend of polyvinylidene fluoride–polyacrilonitrile with an increase in the CNT content, which the authors attributed to the higher roughness of the material’s surface [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FTIR analysis indicated a decrease in the intensity of spectral peaks corresponding to methyl groups ( Figure 3 ), suggesting that the high concentration of CNTs at the films’ surface reduced the number of highly hydrophobic methyl groups of isobutylene. In the study by Shokraei et al [ 49 ], a nanocomposite of multiwalled CNTs and polyurethane nanofibers showed a reduction of the contact angle by increasing the concentration of CNTs as a result of dominant carboxyl groups on the surface. Another study reported an increase in the hydrophobicity of nanocomposites based on a polymer blend of polyvinylidene fluoride–polyacrilonitrile with an increase in the CNT content, which the authors attributed to the higher roughness of the material’s surface [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Shokraei et al aimed to develop an electroconductive scaffold composed of hybrid nanofibers created from simultaneous electrospinning and electrospraying of polyurethane/carbon nanotube (CNT) composites [59]. The inclusion of multi-walled CNTs was shown to increase the conductivity of the scaffold.…”
Section: Polymers and Fabrication Of Electrospun Te Scaffoldsmentioning
confidence: 99%
“…Shrestha et al included functionalized multi-wall CNTs in a polyurethane/silk spinning solution and found conductivities of nearly 60 µS/cm for the resulting nanofiber mats, as compared to values below 1 µS/cm for pure polyurethane (PU) or PU/silk nanofiber mats [24]. Combining electrospraying of polyurethane (PU) with simultaneous electrospraying of multi-wall CNTs, Shokraei et al reached conductivities between 10 −5 and 10 −2 S/cm, as compared to the conductivity of the pure isolating PU of 10 −10 S/cm [25]. Abedi et al report on conductive chitosan/PEDOT:PSS nanofiber mats [26].…”
Section: Electrospinning From Conductive Solutions or Meltsmentioning
confidence: 99%